2019
DOI: 10.3390/ijms20081816
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-214-3p Targeting Ctnnb1 Promotes 3T3-L1 Preadipocyte Differentiation by Interfering with the Wnt/β-Catenin Signaling Pathway

Abstract: Differentiation from preadipocytes into mature adipocytes is a complex biological process in which miRNAs play an important role. Previous studies showed that miR-214-3p facilitates adipocyte differentiation of bone marrow-derived mesenchymal stem cells (BMSCs) in vitro. The detailed function and molecular mechanism of miR-214-3p in adipocyte development is unclear. In this study, the 3T3-L1 cell line was used to analyze the function of miR-214-3p in vitro. Using 5-Ethynyl-2′-deoxyuridine (EdU) staining and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…MiR‑214 was demonstrated to directly interact with the 3'‑UTR of the β‑catenin gene CTNNB1 during osteogenic differentiation of periodontal ligament stem (PDLSC) [ 44 ]. And miR-214 was also demonstrated to target CTNNB1 in human cervical and colorectal cancer cells [ 45 ] and 3T3-L1 pre-adipocyte [ 46 ]. Our result primarily verified circ-PLXNA1/miR-214/CTNNB1 in duck adipocyte but had little influence on triglyceride content and the adipogenic capacity of preadipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‑214 was demonstrated to directly interact with the 3'‑UTR of the β‑catenin gene CTNNB1 during osteogenic differentiation of periodontal ligament stem (PDLSC) [ 44 ]. And miR-214 was also demonstrated to target CTNNB1 in human cervical and colorectal cancer cells [ 45 ] and 3T3-L1 pre-adipocyte [ 46 ]. Our result primarily verified circ-PLXNA1/miR-214/CTNNB1 in duck adipocyte but had little influence on triglyceride content and the adipogenic capacity of preadipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the type and content of bovine adipose tissue directly affects meat tenderness and flavor [22]. miRNAs are important regulators of adipogenesis and lipid metabolism, with some of these miRNAs acting in a pro-adipogenic capacity (e. g., miR-214-3p, miR-20a-5p, and miR-144-3p) [23][24][25], whereas others are anti-adipogenic (e. g., miR-18b-3p, miR-22, and miR-27) [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The miR-214-3p agomir, antagomir, and respective nonspecific control (NC) materials used in this study were purchased from GenePharma (GenePharma, Shanghai, China) and were transfected into GCs with X-treme GENE HP DNA Transfection Reagent (Roche, Mannheim, Germany) at a final concentration of 50 nmol according to the manufacturer's protocol. The medium was changed once after 24 h of transfection [21].…”
Section: Transfection Of Mirna Agomir and Antagomirmentioning
confidence: 99%
“…Research on miR-214-3p tends to center on oncology, skeletal muscle development, adipogenesis, and similar applications [19][20][21]. Sequencing results from the ovarian tissue of Yorkshire pigs have shown that the expression of miR-214-3p in ovary tissues of high-yielding sows is higher than that in low-yielding sows [22].…”
Section: Introductionmentioning
confidence: 99%